1998
DOI: 10.1111/j.1540-8159.1998.tb01163.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ventricular Function by Improving the Activation Sequence During Ventricular Pacing

Abstract: Abnormal electrical activation occurring during ventricular pacing reduces left ventricular (LV) pump function. Two strategies were compared to optimize LV function using ventricular pacing, minimal asynchrony and optimal sequence of electrical activation. ECG and hemodynamics aortic flowprobe, thermodilution cardiac output, LV pressure and its maximal rates of rise (LVdP/dtpos) and fall (LVdP/dtneg) were measured in anesthetized open-chest dogs (n = 7) with healthy hearts. The QRS duration (a measure of async… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
0
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 13 publications
9
69
0
7
Order By: Relevance
“…This dysfunction can be offset by concomitant stimulation of the opposing wall to restore synchrony, and improvement depends on the extent of dyssynchrony generated by the first lead. 17,18 Such observations have suggested that patients with DCM and basal discoordination might benefit from LV or biventricular VDD pacing, and this was recently confirmed. [2][3][4][5] However, the response magnitude varies, highlighting the importance of identifying responsive individuals.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This dysfunction can be offset by concomitant stimulation of the opposing wall to restore synchrony, and improvement depends on the extent of dyssynchrony generated by the first lead. 17,18 Such observations have suggested that patients with DCM and basal discoordination might benefit from LV or biventricular VDD pacing, and this was recently confirmed. [2][3][4][5] However, the response magnitude varies, highlighting the importance of identifying responsive individuals.…”
Section: Discussionmentioning
confidence: 82%
“…Adding an LV free-wall pacemaker (ie, biventricular pacing) improves function, as reported experimentally. 17 We speculate that the major difference in this regard between DCM and normal hearts is that any improvement with recoordination becomes more significant in the former as other functional mechanisms fail.…”
Section: Study Design Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no definite answer to this question, the most likely hypothesis, according to recent experimental and clinical data, 13,14,18,25 is that in patients with LBBB or in animals with experimentally induced LBBB, the LV contractions are totally desynchronized. [25][26][27][28][29] Schematically, the septal area is "akinetic" while the lateral wall is contracting normally but with a marked delay after other areas.…”
Section: Why Is LV Pacing Effective?mentioning
confidence: 99%
“…13,14 Nevertheless, although clinical improvement during permanent BIV pacing has been assessed in randomized 4,5 or prospective observational series, 15 very few results are available on permanent UNI LV pacing. Furthermore, these results were based on a limited number of patients 16 or included a very short-term follow-up.…”
Section: See P 1694mentioning
confidence: 99%